Epiphytic macrolichens as indicators of environmental alteration in northern Thailand - Saipunkaew W. (2014)
Epiphytic lichens were sampled on mango trees (Mangifera spp.) in 32 sites in urban centres and surrounding rural areas in seven provinces of upper northern Thailand. Species were recorded on each tree and frequency estimated in a grid of ten 100-cm2 units. Analysis of macrolichen data showed that lichen diversity was inversely correlated with human population, and that lichen diversity was lowest in the cities with the highest population. The distribution and frequencies of species belonging to families Physciaceae and Parmeliaceae contributed to the groups identified by cluster analysis that corresponded to gradients in rainfall and population density. Comparison with modelled pollution data and local pollution records showed greater correspondence of lichen data with the effects of PM10 than with anthropogenic sulphur. © 2006 Elsevier Ltd. All rights reserved.